Ísland, ferðakort 1:500 000 : ferðakort, nafnaskrá = Iceland 1:500 000, touring map, place name index. - IĐNÚ útgáfa (Landmælingar Íslands, 2015)
17. útgáfa 2015 / IĐNÚ. Road map with tourist features.; Relief shown by shading and spot heights; depths shown by gradient tints.; "Höfundarréttur © Landmælingar Íslands. Copyright © Landmælingar Íslands."; Title from cover.; Accompanied by index booklet: Ísland, nafnaskrá, ferðakort 1:500 000 = Iceland, name index, touring map 1:500 000. 23 pages 20 cm.; Includes notes, 2 small island insets, and publisher's logotype.; Text, outline maps, specimen map, legend, and color illustration on cover. Color; 1:500,000